The impact of the digital and green transitions on investment inefficiency - Francesco Cimini; Fotios Kalantzis (European Investment Bank (EIB), 2024)
This study examines the impact of green and digital investments on the investment inefficiency level of European firms. We define investment inefficiency as the deviation from the optimal investment level, which depends on both the net present value (NPV) of the projects and the marginal benefit and cost of investment. Leveraging matched data from the European Investment Survey (EIBIS) and ORBIS, which results in a sample of 4,892 firmyear observations from 27 European countries surveyed over the period 2021-2023, we employed a panel data regression model to estimate the effect of green and digital investments on investment inefficiency. Our analysis shows that both types of investments reduce investment inefficiency, particularly for under-investing firms. We also find evidence of a statistically significant interaction effect between green and digital investments for over-investing firms, suggesting that digital technologies can enhance the efficiency gains from green investments. Our results have important implications for policy makers and business managers who aim to foster the twin digital and green transition in Europe and improve their investment efficiency and competitiveness.
Keywords: M41; G31; Q53; O33; 330; European Investment Bank Investment Survey; Investment Inefficiency; Green investment; Digital investment; Twin transition